Mesenchymal Stem Cell‐Derived Interleukin 1 Receptor Antagonist Promotes Macrophage Polarization and Inhibits B Cell Differentiation. (31st December 2015) - Luz‐Crawford, Patricia; Djouad, Farida; Toupet, Karine; Bony, Claire; Franquesa, Marcella; Hoogduijn, Martin J.; Jorgensen, Christian; Noël, Danièle
Abstract : The role of interleukin 1 receptor antagonist (IL1RA) in mediating the immunosuppressive effect of mesenchymal stem/stromal cells (MSCs) has been reported in several studies. However, how MSC‐derived IL1RA influences the host response has not been clearly investigated. We therefore derived MSCs from the bone marrow of IL1RA knockout mice and evaluated their immunosuppressive effect on different immune cell subsets. IL1RA deficient ( IL1RA −/− ) or wild type (wt) MSCs inhibited to the same extend the proliferation of T lymphocytes. On the contrary, IL1RA −/− MSCs were less effective than wt MSCs to induce in vitro the macrophage polarization from M1 to M2 phenotype secreting IL10 and exerting a suppressive effect on CD4 + T cells. Moreover compared with wt MSCs, IL1RA −/− MSCs did not efficiently support the survival of quiescent B lymphocytes and block their differentiation toward CD19 + CD138 + plasmablasts secreting IgG antibodies. The effectiveness of IL1RA secreted by MSCs in controlling inflammation was further shown in vivo using the collagen‐induced arthritis murine model. MSCs lacking IL1RA expression were unable to protect mice from arthritic progression and even worsened clinical signs, as shown by higher arthritic score and incidence than control arthritic mice. IL1RA −/− MSCs were not able to decrease the percentage of Th17 lymphocytes and increase the percentage of Treg cells as well as decreasing the differentiation of B cells toward plasmablasts. Altogether, our results provide evidence of the key role of IL1RA secreted by MSCs to both control the polarization of macrophages toward a M2 phenotype and inhibit B cell differentiation in vivo. Stem Cells 2016;34:483–492